The Impact of Artificial Intelligence on Public Sector Decision- Making: Benefits, Challenges, and Policy Implications - Alrawahna, Ammar Salamh; Alzghoul, Amro; Awad, Hussain (International Review of Management and Marketing, 2025)
Artificial intelligence (AI) is increasingly transforming government decision-making processes. This article presents a systematic literature review of 43 studies (2020-2025) examining AI’s impact on public-sector decision-making, delineating its advantages, disadvantages, policy implications, technical aspects, and ethical concerns. The findings indicate that AI technologies offer significant benefits for government decision-making, including improved efficiency, data-driven insights, and enhanced service delivery (e.g., automation of routine tasks and predictive analytics). However, the integration of AI also presents notable drawbacks such as algorithmic bias, transparency deficits, accountability challenges, and ethical dilemmas in public governance. We discuss how these advantages and disadvantages inform policy responses and technical requirements for responsible AI use in the public sector. Key policy implications include the need for robust governance frameworks, regulatory oversight, and ethical guidelines to ensure accountability and public trust. Technical aspects such as data quality, system integration, and explainable AI are identified as critical factors for successful implementation. Ethical concerns—fairness, privacy, transparency, and public value alignment—are examined in light of emerging scholarly debates. The review offers an academically rigorous and up-to-date synthesis to guide researchers, policymakers, and practitioners in understanding the multifaceted impact of AI on government decision-making.